Γ-compactness of some classes of integral functionals depending on vector fields. (July 2023) - Essebei, Fares; Verzellesi, Simone
Abstract: In this paper we achieve some Γ -compactness results for suitable classes of integral functionals depending on a given family of Lipschitz vector fields, with respect to both the strong L p − topology and the strong W X 1, p − topology.